MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) DEVELOPMENT STRATEGIES IN THE PERSPECTIVE OF ISLAMIC ECONOMICS TO IMPROVE THE WELFARE OF STREET TRADERS (CASE STUDY OF STREET VENDORS IN PONTIANAK CITY) - mega putri aliska (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2021)
In Indonesia, one type of business that develops in society is UMKM, which is a business activity that is engaged in various specific business fields. MSMEs are known as efforts that are able to overcome unemployment and poverty, Pontianak City is an area known as the Seramabi Mecca area which is covered with strict regulations in every community activity such as economic activity, so it cannot be denied that every economic activity must be properly monitored. In Pontianak City, MSMEs play an important role in reducing unemployment because the existence of MSMEs can open up large job opportunities so as to improve the welfare of the people. One of the MSMEs that is often run by the community is Livelihood Activities, which are small and medium enterprises that are used to make a living, for example, such as street vendors. In Banda Pontianak, you can find a lot of street vendors who are used as a livelihood, especially in the Pontianak City area, where the increasing number of street vendors appears, of course the more intense the competition that occurs in developing their respective businesses.